PENGARUH PELATIHAN HEXAGONAL OBSTACLE DAN SPRINT SIDE HOP TERHADAP DAYA LEDAK (POWER) OTOT TUNGKAI - Muriasa, Komang (Jurnal Ilmu Keolahragaan Undiksha, 2013)
This study aims to know the effect of sprint training hexagonal obstacle and side hop to the increase in leg muscle explosive power. This type of research is a quasi-experiment with the design of a non-randomized control group pretest-posttest design. Subject students high school football participants ektrakurikuler Study Tour Singaraja school year 2012/2013 amounted to 27 people, and then divided into 3 groups with ordinal pairing technique that has 9 people. Explosive leg muscle power was measured by vertical jump test. Data were analyzed by F test (one way ANOVA) at the significance level (α) = 0.05 with SPSS 16.0. Results of data analysis showed that the treatment group hexagonal obstacle in an increase of 10.22 cm, the treatment group sprint hop side and an increase of 9.33 in the control group increased by 1.22 cm. Results of one way ANOVA test explosive leg muscle power variables between the treatment and control groups gained significance Fcount 9,995 and 0,001. From the results of research and discussion can be concluded: 1). Hexagonal obstacle training and sprint berpengaryh hop side to increase the explosive power of the leg muscles. 2). There is a difference between the effect of hexagonal obstacle training and sprint training side where the hexagonal obstacle hop better. Key words: hexagonal obstacle training, sprint training side hops, leg muscle explosive power.